Plasmodium knowlesi malaria an emerging public health problem in Hulu Selangor, Selangor, Malaysia (2009–2013): epidemiologic and entomologic analysis - Vythilingam, I.; Lim, Yvonne Ai Lian; Venugopalan, B.; Ngui, Romano; Leong, C.S.; Wong, M.L.; Khaw, L.T.; Goh, X.T.; Yap, N.J.; Wan Yusoff, W.S.; Jeffery, J.; Zawiah, A.G.C.T.; et al. (BMC, 2014)
Background: While transmission of the human Plasmodium species has declined, a significant increase in Plasmodium knowlesi/Plasmodium malariae cases was reported in Hulu Selangor, Selangor, Malaysia. Thus, a study was undertaken to determine the epidemiology and the vectors involved in the transmission of knowlesi malaria.